Konstruksi Persepsi Negatif Masyarakat terhadap Cacing Kepala Martil (Bipalium kewense) di Permukiman - Elizabeth Novi Kusumaningrum; Susi Sulistiana; Inggit Winarni; Fawzi Rahmadiyan Zuhairi; Soraya Habibi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The lack of knowledge and information among the public about the characteristics and behavior of hammerhead worms has raised concerns about the dangers to human health when coming into contact with these worms. The purpose of this study is to analyze the formation of negative public perceptions regarding the hammerhead worm Bipalium kewense based on information circulating in online media, as well as to examine its consistency with scientific facts available in the literature. This study was conducted using a narrative literature review approach focused on analysis. The results indicate that the characteristics of the Bipalium kewense worm, such as its morphology, reproductive biology, predation strategies, locomotive organs, toxin content, behavior, and conservation status, indirectly contribute to the formation of negative public perceptions, particularly in residential areas, regarding the presence of this worm. In fact, all these traits, which reflect the worm’s life mechanisms, are forms of biological adaptation commonly found in various groups of invertebrates to ensure their survival. The public’s lack of understanding regarding the life processes of the hammerhead worm leads to these scientific facts being more readily perceived as something terrifying rather than as a natural biological phenomenon. This situation is further fueled by the dissemination of digital information that tends to emphasize the threat aspect rather than providing a balanced scientific explanation. It is concluded that the low level of biological and ecological literacy among residents in residential areas plays a significant role in the formation of misconceptions regarding the presence of B. kewense, as to date, no scientific evidence has been found to indicate that this worm causes.